Protecting electronic information assets. - BALON, Brett (1994)
Identifies potential threats to information assets as (1) internal staff (2) customers (3) industrial spy (4) computer criminals (5) improper garbage disposal (6) social engineering (7) tapping fibre optic cables (8) tapping electromagnetic emmissions from computers. Identifies ways of preventing information theft.